2023
DOI: 10.1212/wnl.0000000000207266
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neighborhood Deprivation With Cognitive and Mood Outcomes in Adults With Pharmacoresistant Temporal Lobe Epilepsy

Abstract: Background and ObjectivesTemporal lobe epilepsy (TLE) is the most common adult form of epilepsy and is associated with a high risk of cognitive deficits and depressed mood. However, little is known about the role of environmental factors on cognition and mood in TLE. This cross-sectional study examined the relationship between neighborhood deprivation and neuropsychological function in adults with TLE.MethodsNeuropsychological data were obtained from a clinical registry of patients with TLE and included measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Overall, Busch et al 5 suggested that the ADI was associated with neuropsychological functioning in this cross-sectional complete case analysis. Additional prospective studies with valid and comprehensive longitudinal data are needed to address the methodological limitations (e.g., selection, confounding, and information biases) observed in this descriptive study.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Overall, Busch et al 5 suggested that the ADI was associated with neuropsychological functioning in this cross-sectional complete case analysis. Additional prospective studies with valid and comprehensive longitudinal data are needed to address the methodological limitations (e.g., selection, confounding, and information biases) observed in this descriptive study.…”
mentioning
confidence: 53%
“…2,3 Although substantial research has documented disparities in individual-level social needs in people with epilepsy, scant research exists examining associations between community-level SDOH and epilepsy outcomes. [3][4][5] In this issue of Neurology ® , Busch et al 5 publish a study that examined the associations between neighborhood deprivation and neuropsychological function in older adolescents and adults with temporal lobe epilepsy (TLE), primarily from Ohio and surrounding states. The authors are commended for conducting a timely study aimed at bringing greater attention to the role of SDOH on neurologic status and outcomes.…”
mentioning
confidence: 99%
“…We hypothesize that this is likely due in large part to social and environmental factors, as we have recently shown that neighborhood disadvantage (as assessed by the Area Deprivation Index) is associated with cognitive phenotype in TLE. 47 Further studies, in more diverse clinical samples, are needed to better understand these complex relationships. Finally, research has shown improvements in cognition with amelioration of mood and anxiety symptoms in individuals with depressive disorders.…”
Section: Limitationsmentioning
confidence: 99%
“…Given the detrimental effects of depression, it is imperative to increase research on potential treatments and interventions 14,15 . Lifestyle changes, including diet and exercise, have been identified as potential avenues for treatment 16–20 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the detrimental effects of depression, it is imperative to increase research on potential treatments and interventions. 14,15 Lifestyle changes, including diet and exercise, have been identified as potential avenues for treatment. [16][17][18][19][20] In addition, there is a growing body of evidence on specific nutritional targets that are inversely associated with depression.…”
Section: Introductionmentioning
confidence: 99%